Sulfate reduction controlled by organic matter availability in deep sediment cores from the saline, alkaline Lake Van (Eastern Anatolia, Turkey) - Clemens eGlombitza; Mona eStockhecke; Carsten J. Schubert; Alexandra eVetter; Jens eKallmeyer (Frontiers in Microbiology, 2013)
As part of the International Continental Drilling Program (ICDP) deep lake drilling project PaleoVan, we investigated sulfate reduction (SR) in deep sediment cores of the saline, alkaline (salinity 21.4 ‰, alkalinity 155 m mEq-1, pH 9.81) Lake Van, Turkey. The cores were retrieved in the Northern Basin (NB) and at Ahlat Ridge (AR) and reached a maximum depth of 220 m. Additionally, 65-75 cm long gravity cores were taken at both sites. Sulfate reduction rates (SRR) were low (≤ 22 nmol cm-3 d-1) compared to lakes with higher salinity and alkalinity, indicating that salinity and alkalinity are not limiting SR in Lake Van. Both sites differ significantly in rates and depth distribution of SR. In NB, SRR are up to 10 times higher than at AR. Sulfate reduction (SR) could be detected down to 19 meters below lake floor (mblf) at NB and down to 13 mblf at AR. Although SRR were lower at AR than at NB, organic matter (OM) concentrations were higher. In contrast, dissolved OM in the pore water at AR contained more macromolecular OM and less low molecular weight OM. We thus suggest, that OM content alone cannot be used to infer microbial activity at Lake Van but that quality of OM has an important impact as well. These differences suggest that biogeochemical processes in lacustrine sediments are reacting very sensitively to small variations in geological, physical or chemical parameters over relatively short distances.